Can low intensity cognitive behavioural therapy for non‐cardiac chest pain presentations to an emergency department be efficacious? A pilot study. (17th July 2019) - Wilkinson, Megan; Venning, Anthony; Redpath, Paula; Ly, Marleesa; Brown, Sharon; Battersby, Malcolm
Abstract: Objective: Complaints of chest pain are one of the most common reasons that people visit emergency departments (EDs). However, more than 50% of patients who present to EDs with chest pain do not have identifiable cardiac disease or other medical conditions. A pilot study was conducted to investigate if using low‐intensity (LI) cognitive behavioural therapy (CBT) in the ED at Flinders Medical Centre, South Australia, reduced the reported levels of anxiety and depression, re‐presentation rates, and the associated cost of patients presenting to the ED with non‐cardiac chest pain. Method: A convenience sample ( n = 35) was recruited from people who presented to the ED with non‐cardiac chest pain and screened positive for psychological distress. If eligible, participants were referred to the Improving Access to Psychological Therapies@Flinders (IAPT@Flinders) service and, following completion, hospital medical records were reviewed to investigate the number of presentations to the ED and the subsequent costs of each presentation, in the 3 months prior and 3 months preceding treatment. Results: There was a decrease in self‐reported levels of depression and anxiety after the completion of treatment, and a suggested 59% decrease in ED admissions and a 69% cost saving. Conclusions: The potential health benefits and cost savings as a result of LICBT for patients who present to ED's with non‐cardiac chest pain warrant further investigation utilising a robust and economically validated trial.